Pioneer translation products as an alternative source for MHC-I antigenic peptides. Issue 2 (December 2015) - Apcher, Sebastien; Daskalogianni, Chrysoula; Fåhraeus, Robin
Highlights: PTPs are produced from newly synthesized mRNAs in the nuclear compartment. The presentation of PTP-derived antigenic peptides is dependent, just like in the case of exon-derived peptides, of the proteasome and TAP. The PTPs offers an explanation to different observations of CD8 T cells toward epitopes derived from introns, intron/exon junctions, 5′ and 3′ untranslated regions. Abstract: The notion that alternative peptide substrates can be processed and presented to the MHC class I pathway has opened for new aspects on how the immune system detects infected or damaged cells. Recent works show that antigenic peptides are derived from intron sequences in pre-mRNAs target for the nonsense-mediated degradation pathway. Introns are spliced out co-transcriptionally suggesting that such pioneer translation products (PTPs) are synthesized on the nascent RNAs in the nuclear compartment to ensure that the first peptides to emerge from an mRNA are destined for the class I pathway. This illustrates an independent translation event during mRNA maturation that give rise to specific peptide products with a specific function in the immune system. The characterization of the translation apparatus responsible for PTP synthesis will pave the way for understanding how PTP production is regulated in different tissues under different conditions and will help designing new vaccine strategies.